ANALISIS PENYELESAIAN SENGKETA TUMPANG TINDIH LAHAN ANTARA PT BIB DENGAN PEMEGANG SURAT KETERANGAN TANAH DI KABUPATEN TANAH BAMBU - Hartana (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
The formulation of land and natural resources in a concise and philosophical substance is contained in Article 33 Paragraph (3) of the 1945 Constitution which reads: Earth and air and the natural resources contained therein are controlled by the State and used for the greatest prosperity of the people . Land does not only have high economic value, but also philosophical, political, social and cultural values. It is not surprising that land is a special treasure that continuously triggers various complex and complicated social problems. In this study, the type of research used is library research. The option of resolving disputes through settlement/mediation has advantages when compared to litigation in front of a court which is not attractive in terms of time, cost, and thought/energy. In addition, the lack of trust in court settlement and the administrative constraints that surround it, make the court the last resort for dispute resolution. Mediation gives parties a feeling of comfortable position and attempts to buy the final result of the agreement reached by mutual agreement without pressure and coercion